An Investigation of the Interaction Patterns of Peer Patrons on an Online Peer-Support Portal for Informal Caregivers of Alzheimer's Patients. Issue 4 (2nd October 2019) - Narasimha, Shraddhaa; Wilson, Mackenzie; Dixon, Emma; Davis, Nicole; Madathil, Kapil Chalil
Abstract: Online peer support portals are an effective way for informal caregivers to obtain support from the comfort of their homes. Having realized a dearth of research focusing on users of healthcare peer-support portals, this study focused on top contributors, termed as 'peer patrons', on one such portal. In order to understand their contribution in helping caregivers cope with their situation and to investigate any unique patterns of interaction, a qualitative thematic analysis was carried out on 1405 openly available comments on an online peer support group for informal caregivers of Alzheimer's patients. The analysis revealed five themes related to content of peer patrons' interaction with other portal members - Advice provider, information source, shoulder to cry on, portal star, and caregiver advocate. An additional theme related to the structure of the responses by peer patrons was also uncovered. In order to explain their contribution to these portals, parallels were drawn between the Stress and Coping model as applied to Dementia caregivers to show that peer patrons may be contributing towards caregivers' coping mechanisms.